2007
DOI: 10.1093/jn/137.1.216s
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Deficiency, Alterations in Global Histone Modifications, and Carcinogenesis

Abstract: The methyl-deficient model of endogenous hepatocarcinogenesis in rodents is unique in that dietary omission rather than the addition of chemical carcinogens leads to tumor formation. Thus, the biochemical and molecular events predisposing to cancer in this model result from chronic metabolic stress and provide an ideal model system to study progressive alterations that occur during carcinogenesis. Moreover, epigenetic alterations imposed by this diet are believed to be 1 of the main mechanisms responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 62 publications
1
76
0
1
Order By: Relevance
“…This was accompanied by a global increase in both H4K16Ac and H3K9me3 and with a decrease in H4K20me3 and H3K9Ac (Pogribny et al, 2007). Although these findings argue in favor of H4K16 hypoacetylation being a phenomenon of cellular transformation, a caveat to these studies is that this specific model of MDDpromoted tumorigenesis in rat livers is due to metabolic deficiency and it might be mechanistically very peculiar compared to the rest of cancers.…”
Section: Sirts Cancer and H4k16mentioning
confidence: 79%
“…This was accompanied by a global increase in both H4K16Ac and H3K9me3 and with a decrease in H4K20me3 and H3K9Ac (Pogribny et al, 2007). Although these findings argue in favor of H4K16 hypoacetylation being a phenomenon of cellular transformation, a caveat to these studies is that this specific model of MDDpromoted tumorigenesis in rat livers is due to metabolic deficiency and it might be mechanistically very peculiar compared to the rest of cancers.…”
Section: Sirts Cancer and H4k16mentioning
confidence: 79%
“…Folate deficiency occurs in about 10% of the US population and low folic acid has been associated with chromosomal damage, including strand breaks and misincorporation of uracil into DNA (Blount et al, 1997;Duthie and Hawdon, 1998;Pogribny et al, 2006b). Folic acid deficiency was linked to the formation of NTDs by the observation that pregnant women who took medication that interfered or antagonized folate metabolism (aminopterin, carbamazpine, and valproic acid) had a greater number of children with spina bifida (Johnson et al, 1999).…”
Section: Understanding the Causes Of Ntdsmentioning
confidence: 99%
“…There are currently 24 known sites of methylation: 17 on lysine residues and seven on arginine residues (Pogribny et al, 2006b). Pogribny et al fed rats a methyl deficient diet (MDD) and found a significant decrease in trimethylation of histone3-lysine9 (H3K9) and histone4-lysine20 (H4K20); H3K9 trimethylation is necessary for cells to differentiate and its loss favors proliferation.…”
Section: Protein Methylation and Ntdsmentioning
confidence: 99%
See 2 more Smart Citations